Wanted - Platt, Marc; Bekmambetov, Timur; Universal Pictures; Spyglass Entertainment (California : Universal Studios Home Entertainment, 2008)
A young man finds out his long lost father is an assassin. When his father is murdered, the son is recruited into his father's old organization and trained by a man named Sloan to follow in his dad's footsteps
Title from title screen
Bonus disc: Extended scene, cast and characters, stunt on the L Train, special effects: the art of the impossible
Based on the comic book series created by Mark Millar and J.G. Jones
Director of photography, Mitchell Amundsen ; editor, David Brenner ; music, Danny Elfman
Cast: James McAvoy, Morgan Freeman, Angelina Jolie, Terence Stamp
DVD Format
Keywords: Parents -- Death -- Drama; Secret societies -- Drama; Revenge -- Drama